Navigating international academia : research student narratives - Brown, Jill (Jillian Roberta) (Sense Publishers, 2014)
These narratives recount what it means to be a research student at an Australian university. They unpack the complex pathways that have lead the authors to this place, the early imaginings, the attempts to achieve the dream and the challenges that come with that achievement. These students bring a range of life skills and experiences to their studies and need to balance competing financial, family and employment related demands on their time and attention. For the international students whose voices dominate this text, there are also barriers of culture, language and physical and emotional dislocation. Students from Vietnam, Indonesia, Bangladesh, Iraq and Romania recount the personal and academic challenges they have faced and the ways in which they have struggled to find a way of being in academia which both accommodates their sense of self and allows them to be recognised as researchers in the international arena. An Australian student adds her voice to the collection. Their stories all combine the intensely personal with the academic. There is the joy of finding libraries full of books, of making friends with strangers, of managing to be student, partner and parent. There is pride in the achievement of children coping with school and gratitude for the support of family and fellow students. There is also developing confidence in their ability to contribute to research in the international arena and increasing authority in the ownership of their research. As a collection these narratives offer insight into both the student travellers and the academic and personal journeys being taken. Cover photo: International academia, by Erika Akerlund, Hobart, Australia.